2016
DOI: 10.1016/j.matdes.2016.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Direct fabrication of high-performance high speed steel products enhanced by LaB 6

Abstract: A direct fabrication technology (DFT) without smelting has been developed for fabricating sophisticated high speed steel products with low pollution, near-net shaping and short process. The steel consisting of (wt. %): 6.4W, 5.0Mo, 4.2Cr, 3.1V, 8.5Co and 1.28C, was fabricated as exemplary material. The activated and reactive sintering of green compacts under vacuum with low activation energy, redox reaction enhanced diffusion and the construction of concentration gradient of alloying elements around pores, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 45 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…The diffusion coefficient of chromium is much higher than that of tungsten, chromium and vanadium. Therefore, chromium carbide is the first to dissolve, and completely dissolved at 1180°C, which is consistent with the report [14]. The evolution of M 6 C and M 2 C carbides is mainly affected by tungsten and molybdenum.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The diffusion coefficient of chromium is much higher than that of tungsten, chromium and vanadium. Therefore, chromium carbide is the first to dissolve, and completely dissolved at 1180°C, which is consistent with the report [14]. The evolution of M 6 C and M 2 C carbides is mainly affected by tungsten and molybdenum.…”
Section: Discussionsupporting
confidence: 91%
“…During the sintering process, the types of carbides had undergone an interesting evolution, and the original carbides gradually transformed into composite carbides. Zhang et al [14] pointed out that M 6 C carbides start to form at 1000°C. In this paper, it is observed that a large amount of white M 6 C carbides in the samples after sintered at 1180°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frictional wear mechanism of pure M2HSS with different TiC addition was described as follows. The wear resistance of the pure M2HSS material relied mainly on fine carbide grains such as WC, MoC, and VC, which were diffusely distributed in the matrix [44][45][46][47][48][49][50][51][52][53] with a grain size in the matrix ranging from 1 to 2 μm. When the grinding ball was applied to the sample surface with a normal load and shear force, the grains of M2HSS were pulled off, and the fragmentation is shown in Figure 12a.…”
Section: Hardness and Friction Propertiesmentioning
confidence: 99%
“…Therefore, many efforts have been reported focusing on the preparation of HSS with water atomised powders. The studies on how to achieve pressureless sintering of HSS have received extensive attention due to their low cost [11,12]. Giménez et.al studied the microstructure characteristics of HSS fabricated by HIP, vacuum sintering, and nitrogen sintering [13].…”
Section: Introductionmentioning
confidence: 99%